2021
DOI: 10.1113/ep089673
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise increases global and gene‐specific (interleukin‐17 and interferon‐γ) DNA methylation in lymphocytes from aged women

Abstract: Ageing-induced increase in inflammatory gene expression through a reduction in DNA methylation might contribute to chronic diseases. Regular physical exercise practices, in turn, are associated with a decrease in the incidence of inflammatory diseases. We herein evaluated the effects of three exercise modalities on lymphocyte global and gene-specific (interferon γ (IFN-γ) and interleukin 17A (IL-17A) DNA methylation in aged women (68 ± 7.5 years). This cross-sectional study included 86 women, divided into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Studies suggest that PA is associated with DNA hypermethylation (although these results are not unanimous), contributing to a decreased expression of inflammation-related genes (such as the hypermethylation of IL-17A and IFN-γ promoter regions or TNF gene and the hypomethylation of IL-10) [ 311 ]. Exercise can also induce histones acetylation/deacetylation in a body mass index-dependent manner [ 312 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggest that PA is associated with DNA hypermethylation (although these results are not unanimous), contributing to a decreased expression of inflammation-related genes (such as the hypermethylation of IL-17A and IFN-γ promoter regions or TNF gene and the hypomethylation of IL-10) [ 311 ]. Exercise can also induce histones acetylation/deacetylation in a body mass index-dependent manner [ 312 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results corroborate with previously literature. Machado et al, 2021 evidenced that the methylation levels in promoter regions of IL-17A gene was higher in participants that were submitted to exercise program when compared to the control group ( 8 ). According to the authors, the exercise-induced increase of DNA methylation in inflammatory genes could be related to loss of immune function ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that some cluster of genes associated with obesity appear unchanged following surgical procedure ( 4 ), warranting the search for others therapies capable of boosting the benefits of bariatric surgery. In this regard, exercise training emerges as a potential adjuvant therapy able to modulate DNA methylation of distinct genes related to adipocyte metabolism ( 7 ) and inflammatory responses ( 8 ), with were related to reduced risk of chronic diseases ( 9 ). Study evaluating the effects of three exercise modalities on DNA methylation levels observed that the practice of resistance training increased global DNA methylation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention studies in older women confirmed the earlier trend and showed a significant increase in global leukocyte methylation with resistance and aerobic exercises. Increased DNA methylation negatively correlated with the time of performing the exercise protocol, i.e., people with better physical condition, which translated into more efficient exercise, had higher DNA methylation compared to sedentary women [ 31 ].…”
Section: Global Methylationmentioning
confidence: 99%